Lie Supergroups Obtained from 3-Dimensional Lie Superalgebras Associated to the Adjoint Representation and Having a 2-Dimensional Derived Ideal. (25th November 2007) - Hernández, I.; Peniche, R.
Abstract : We give the explicit multiplication law of the Lie supergroups for which the base manifold is a 3-dimensional Lie group and whose underlying Lie superalgebrag = g 0 ⊕ g 1 which satisfiesg 1 = g 0, g 0 acts ong 1 via the adjoint representation andg 0 has a 2-dimensional derived ideal.